Job loss as a blessing in disguise : The role of career exploration and career planning in predicting reemployment quality - Zikic, Jelena; Klehe, Ute-Christine; Justus Liebig University Giessen (My University, 2006)
Job loss is one of the most difficult work related situations that an individual may encounter. Yet, sometimes job loss may also turn into a blessing in disguise. Combining the careers literature with the literature on unemployment, the current paper addresses potential positive outcomes of job loss by focusing on specific career adaptability activities that individuals can undertake to obtain these outcomes. Three hundred and four unemployed outplacement attendees reported their use of self and environmental career exploration and career planning, as well as of job search (general and networking) and the availability of two resources that may foster these activities, general self-efficacy and social support. Six months later, 215 individuals reported their current reemployment status and, when applicable, the quality of that reemployment. Results replicate the positive effects of job search on finding reemployment but moreover outline the relevance of career planning and exploration during unemployment on ensuring the quality of this reemployment. Theoretical implications and directions for practice and future research are discussed.
Keywords: unemployment; job loss; job search strategy; career adaptability activity; ddc:150